(untitled) (American Scholar: Journal of Interdisciplinary Research and Knowledge, 2026)
In pharmacotherapy (also in phytotherapy), it is often necessary to use several drugs at the same time. The main goal is to achieve a faster and stronger pharmacotherapeutic effect or to increase the effectiveness of drugs by affecting several organ systems and reducing their side effects. As a result of the simultaneous introduction or sequential administration of several drugs into the body, their effects may change in various ways. When several drugs are used in this way, synergism or antagonism may occur